2020
DOI: 10.1002/adem.202000910
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the Near Eutectic Aluminum–Silicon Alloy with Graphene: An Approach toward Self‐Lubricating Composite

Abstract: Mechanical and physical properties of aluminum alloys make them suitable for automotive and other structural applications. The high silicon content in aluminum improves the hardness to a great extent but at the cost of ductility. Herein, the reinforcement of near eutectic Al–Si (ADC12) alloy with the reduced graphene oxide (rGO) is demonstrated. The ADC12 alloy and its composite with rGO are cast using the gravity stir die‐casting process. The structural, mechanical, metallurgical, and tribological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…From the static microhardness results, it can be concluded that Al 13 (Fe, Cr) 4 and QC Al 91 Fe 4 Cr 5 could act as the reinforcement phase for this QC/Al composite. [38]. The detailed explanation of these results and the intimacy of the contact is introduced in Sec.…”
Section: 1mentioning
confidence: 96%
“…From the static microhardness results, it can be concluded that Al 13 (Fe, Cr) 4 and QC Al 91 Fe 4 Cr 5 could act as the reinforcement phase for this QC/Al composite. [38]. The detailed explanation of these results and the intimacy of the contact is introduced in Sec.…”
Section: 1mentioning
confidence: 96%
“…[8] To improve wear problem of Al-alloy workpieces at high temperatures, developing novel and efficient self-lubricating Al-matrix composites has attracted widespread attention. [9,10] At present, there are two main strategies for designing and preparing self-lubricating Al-matrix composites. One is surface treatment, i.e., depositing solid self-lubricating films on the composite surface by anodizing, [11] microarc oxidation, [12] pulsed laser deposition, [13] electrical discharge alloying, [14] and plasma electrolytic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] To improve wear problem of Al‐alloy workpieces at high temperatures, developing novel and efficient self‐lubricating Al–matrix composites has attracted widespread attention. [ 9,10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Among several Al alloys, ADC12 (Al-Si-Cu) alloy is a conventional cast alloy applied to power train and transmission cases due to its high castability with a low shrinkage rate [7][8][9]. Nevertheless, ADC12 has a brittle nature because of the formation of intermetallic phase containing Si element [7,[10][11][12][13]. Recently, high-Zn Al-based-alloys have attracted much research interest as a promising Al-cast alloy for automotive applications.…”
Section: Introductionmentioning
confidence: 99%